The Causal Effects of Primary Biliary Cholangitis on Thyroid Dysfunction: A Two-Sample Mendelian Randomization Study - Huang, Peng; Hou, Yuqing; Zou, Yixin; Ye, Xiangyu; Yu, Rongbin; Yang, Sheng (Frontiers in Genetics, 2021)
Background: Primary biliary cholangitis (PBC) is an autoimmune disease and is often accompanied by thyroid dysfunction. Understanding the causal relationship between PBC and thyroid dysfunction is helpful to explore the pathogenesis of PBC, and to develop strategies for the prevention and treatment of PBC and its complications. Methods: We used a two-sample Mendelian randomization method to estimate the causal effect of PBC on the risk of autoimmune thyroid disease (AITD), thyroid-stimulating hormone (TSH) and free thyroxine (FT4), hyperthyroidism, hypothyroidism, and thyroid cancer (TC) in European population. We collected seven datasets of PBC and related traits to perform a series MR-analysis and performed extensive sensitivity analyses to ensure the reliability of our results. Results: Using sensitivity analysis, we found that PBC was a risk factor for AITD, TSH, hypothyroidism and TC with odds ratio (OR) 1.002 (95% CI: 1.000-1.005, P=0.042), 1.016 (95% CI: 1.006-1.027, P=0.002), 1.068 (95% CI: 1.022-1.115, P=0.003) and 1.106 (95% CI: 1.019-1.120, P=0.042), respectively. Interestingly, using reverse-direction MR analysis, we also found that AITD had significantly potential causal association to PBC with OR 0.021 (P=5.10E-4) and that other two had no significant casual relation on PBC. Conclusion: PBC causes thyroid dysfunction, specifically as AITD, mild hypothyroidism and TC. The causal relationship between PBC and thyroid dysfunction provides a new direction for the etiology of PBC.